Two Men and Nine Years: Contribution of Karsten Jacobsen and Gürcan Büyüksalih to Photogrammetry and Remote Sensing Activities of Department of Geomatics Engineering at Zonguldak Bülent Ecevit University - H. Topan; H. Akçın; M. Oruç; A. M. Marangoz; C. Atalay; Ç. Bayık (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The millennium witnessed the development of high resolution remote sensing technology and its role in the geospatial information extraction. These developments required the photogrammetric evaluation of these images. Thanks to Dr. Gürcan Büyüksalih’s attending to the Department of Geomatics Engineering at Zonguldak Bülent Ecevit University at the beginning of 1998, the education and research studies were started initiated under the guidance of a full-faculty member of the Department. After three years of preparation, a bilateral international project leading in its field was started in cooperation with Dr. Karsten Jacobsen. This paper reviews the contribution of two men to a wide range of photogrammetry and remote sensing activities in the Department of Geomatics Engineering at Zonguldak Bülent Ecevit University between 1998 and 2007. These studies involved not only the high resolution remote sensing images such as SPOT-5, IRS-1C, IKONOS, QuickBird, OrbView-3, Kompsat-1, Landsat but also the optical analogue images such as TK-350, KVR-1000 and MOMS-2P, and microwave data such as SRTM and JERS in terms of geometric analysis, georeferencing accuracy assessment, DSM/DEM generation and validation, and information content for topographic mapping. Thanks to this bilateral co-operation, the concept of mapping from space was developed and supported by many international scientists, making a very important contribution to the development of advanced remote sensing. These research activities were extended by bilateral Erasmus agreements, bilateral academic visits, two training courses which were the first in Türkiye, participation in various national and international scientific events, organisation of an ISPRS workshop and official duties in ISPRS working group.